Mixed Finite Element Method for Dirichlet Boundary Control Problem Governed by Elliptic PDEs - Gong, Wei; Yan, Ningning (SIAM journal on control and optimization, 2011)
In this paper we study the finite element approximation of Dirichlet boundary control problems governed by elliptic PDEs. Based on a mixed variational scheme, we establish a mixed finite element approximation to the underlying optimal control problem. We consider the optimal control problems posed on both polygonal and general smooth domains, and we derive a priori error estimates for optimal control, state, and adjoint state. The optimal and quasi-optimal error estimates are obtained for problems on polygonal and smooth domains, respectively. Numerical experiments are provided to confirm our theoretical results.